Life cycle research on the carbon budget of the Larix principis-rupprechtii plantation forest ecosystem in North China. (10th March 2018) - Lun, Fei; Liu, Yu; He, Lu; Yang, Lun; Liu, Moucheng; Li, Wenhua
Abstract: Plantation forests play an important role in global carbon cycle. However, life cycle analysis on carbon budget of plantation forests was still poorly documented, especially regarding how forest management influence its carbon dynamics. Therefore, this study aims to bridge this gaps, taking Larix principis-rupprechtii plantation forest in North China for example. Based on established tree growth models and carbon stock models, we firstly discussed carbon dynamics of living trees; besides, carbon budgets of forest litter and soil were estimated by balancing its carbon inputs and carbon emissions (using the YASSO model). Forest management (including seedlings, site preparation and logging) can lead to carbon emissions due to material and energy consumption. Our findings were as follows: carbon sequestration by plantation forest amounted to 164.56 t C/ha during one 41-year rotation period in our study, most of which flowed into forest litter and soil. During one whole rotation period, forest litter and soil released out 100.21 tC/ha of sequestered carbon, while forest management resulted in about 1.59 tC/ha of carbon emissions. With forest plantation renewal, forest carbon storage increased due to more carbon stored in forest litter and soil, mainly existing in humus 1 and humus 2. Considering forest natural carbon dynamics, plantation forest functioned as the "carbon sink" during the first 5 rotation periods in our study, but the net carbon sink decreased from 35.95 tC/ha to 0.98 tC/ha. The increase of temperature and precipitation could result in more carbon emissions, and forest ecosystem carbon budget was more sensitive to precipitation changes than that to temperature changes.